Engage with people with disabilities for well-being and happiness - Professor Dr. Ruzita - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 24 March 2021 - Who would have thought that being born in perfect condition, a person can be called a people with disabilities (OKU) when misfortune strikes.